The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.2478/bjmg-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Obsessive Compulsive Disorder And Tumor Necrosis Factor-Α Gene –308 (G>A) And –850 (C>T) Polymorphisms In Turkish Children

Abstract: Obsessive compulsive disorder (OCD) is a neurobiological disease characterized with obsessions and compulsions. Obsessive compulsive disorder occurs with an autoimmune mechanism after Group A β hemolytic streptococcus (GABHS) infection. Tumor necrosis factor (TNF) is an important cytokine, as well as having an important role in the apoptosis mechanism of autoimmune diseases. It is expressed by the TNF-α gene. The aim of this study was to examine the relationship between the TNF-α gene promoter region −308 (G>A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The first finding—that TNF‐ α −1031T/C is not significantly associated with the development of schizophrenia—is consistent with two prior studies conducted on a similar Han Chinese population demonstrating that a number of TNF‐ α single nucleotide polymorphisms, such as −238G/A, −308G/A, −857C/T, and −863C/A are not more or less prevalent in schizophrenia as compared to controls (Duan et al, ; Srinivas et al, ). However, some other studies reported that TNF‐ α −308G/A allele is a risk factor for schizophrenia when examined in North Indian, Saudi, Turkish, Pakistani, and Korean populations, indicating a possible interaction between genetic background and environment (Handoko et al, ; Kadasah, Arfin, Rizvi, Al‐Asmari, & Al‐Asmari, ; Luleyap et al, ; Pae et al, ). One main explanation for this discrepancy on the association between TNF‐ α −1031T/C polymorphism and the susceptibility to schizophrenia may be due to ethnic difference, since it appears that the allele frequency of the variant allele C varied markedly from different ethnicities (Duan et al, ; Handoko et al, ; Kadasah et al, ; Luleyap et al, ; Pae et al, ; Srinivas et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first finding—that TNF‐ α −1031T/C is not significantly associated with the development of schizophrenia—is consistent with two prior studies conducted on a similar Han Chinese population demonstrating that a number of TNF‐ α single nucleotide polymorphisms, such as −238G/A, −308G/A, −857C/T, and −863C/A are not more or less prevalent in schizophrenia as compared to controls (Duan et al, ; Srinivas et al, ). However, some other studies reported that TNF‐ α −308G/A allele is a risk factor for schizophrenia when examined in North Indian, Saudi, Turkish, Pakistani, and Korean populations, indicating a possible interaction between genetic background and environment (Handoko et al, ; Kadasah, Arfin, Rizvi, Al‐Asmari, & Al‐Asmari, ; Luleyap et al, ; Pae et al, ). One main explanation for this discrepancy on the association between TNF‐ α −1031T/C polymorphism and the susceptibility to schizophrenia may be due to ethnic difference, since it appears that the allele frequency of the variant allele C varied markedly from different ethnicities (Duan et al, ; Handoko et al, ; Kadasah et al, ; Luleyap et al, ; Pae et al, ; Srinivas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some other studies reported that TNF‐ α −308G/A allele is a risk factor for schizophrenia when examined in North Indian, Saudi, Turkish, Pakistani, and Korean populations, indicating a possible interaction between genetic background and environment (Handoko et al, ; Kadasah, Arfin, Rizvi, Al‐Asmari, & Al‐Asmari, ; Luleyap et al, ; Pae et al, ). One main explanation for this discrepancy on the association between TNF‐ α −1031T/C polymorphism and the susceptibility to schizophrenia may be due to ethnic difference, since it appears that the allele frequency of the variant allele C varied markedly from different ethnicities (Duan et al, ; Handoko et al, ; Kadasah et al, ; Luleyap et al, ; Pae et al, ; Srinivas et al, ). The additional factors such as heterogeneity of the schizophrenia diagnosis, small gene effects, and population stratification may be also involved.…”
Section: Discussionmentioning
confidence: 99%
“…In many multifactorial and single gene neurodegenerative disorders, the symptoms are similar, but also these are the common characteristics of polygenic traits. [45] In addition, there are symptoms which differ from patient-to-patient. For that reason, simultaneous expression profiles of immune system genes should be investigated as well.…”
Section: Discussionmentioning
confidence: 99%
“…() using an extended patient population (the number of OCD cases increased from 111 to 183), whereas the association between the ‐308 A‐allele and OCD has not been verified. The ‐308 A‐allele and AA genotype, however, was much more frequent among 45 OCD patients compared to 58 controls in a Turkish study (Lüleyap et al ., ). One of the possible reasons behind the contradictory findings could be the different allele frequencies in the studied populations: the frequency of the minor ‐308 A‐allele was much lower in the Turkish and Brazilian control groups (4.3% and 9%, respectively) compared to Caucasian populations [see the CEU panel with 17.3% (http://www.ncbi.nlm.nih.gov/snp/), the Hungarian control sample with 15.2% (Table ), or the mainly Caucasian Canadian sample with 13.2% (Zai et al ., )].…”
Section: Discussionmentioning
confidence: 99%